PENGARUH PROMOSI DENGAN MENGGUNAKAN WEBSITE TERHADAP VOLUME PENJUALAN DI WISATA AGRO MERAPI FARMA HERBAL YOGYAKARTA - Rudi Kurniawan (Jurnal Dinamika Sosial Ekonomi, 2010)
BUDI KURNIAWAN The Promotion Effect Using Website on Sales Volume at Wisata Agro Merapi Farma Herbal Yogyakarta. Supervised by JUARINI and HENI HANDRI UTAMI. The research aims to know the effect of promotion using website on sales volume at Merapi Farma Herbal Yogyakarta and the Promotion effectivity using website compare with promotion using leaflet. The research method use case method used a secondary data. The analysis of the promotion using website use linear regression method and to know the promotion effectivity between website and leafletuse effectivity formula. The research showed that the promotion using website effected significantly to the Sales volume of Merapi Farma Herbal Yogyakarfa and the Promotion using website is more effective than the Promotion using leaflet.Keyword : Promotion, website, sales volume, effectivityAlgifari, 1997. Analisis Statistika untuk Bisnis. BPFE. Jakarta